Evolutionary analyses of HIV-1 protein-coding sequences : adaptation to host cytotoxic immune responses and purifying selection at synonymous sites - Ngandu, Nobubelo Kwanele (Department of Molecular and Cell Biology, 2014)
Includes abstract.